A new solvothermal approach to obtain nanoparticles in the Cu3SnS4-Cu2FeSnS4 join - Giaccherini,A.; Griesi,A.; Montegrossi,G.; Romanelli,M.; Lepore,G.O.; Lavacchi,A.; Amthauer,G.; Redhammer,G.; Tippelt,G.; Martinuzzi,S.; Cucinotta,G.; Mannini,M.; et al. (Journal of Geosciences, 2020)
In the field of the renewables, a large effort has been devoted in the last years to obtain conventional and new materials for solar energy conversion by using methods which couple a good efficiency and scalability with energetic and environmental concerns. This research has included the so-called kesterites, materials considered interesting for the thin film solar cell technology, consisting of relatively abundant and harmless elements: Cu3-x-yFexZnySn(S,Se)4.In this study, we undertook the synthesis of members of the kuramite-stannite (Cu3SnS4-Cu2FeSnS4) join by means of a two-step solvothermal approach, able to provide nanocrystalline products in an easy, low-temperature, and fast way. The sample with the highest Fe concentration was characterised by means of a multi-analytical approach, aimed to assess not only its final structural, chemical and micromorphological features, but also the redox speciation of the two transition metal cations, i.e. Cu and Fe, in relation to the overall charge balance. Namely, Electron Paramagnetic Resonance (EPR), Mössbauer and X-ray Absorption Spectroscopy (XAS) and SQUID magnetometry were involved. The main results point out an excellent control of the structural features, and an intermediate Fe content in the sample, leading to the following formula unit: Cu2.2Fe0.48Sn1.2S4. The overall findings of the multi-analytical characterization imply a complex redox balance, where inferring the site occupancy is not trivial; the charge balance, in fact, can only be achieved taking into account the presence of both Fe(III) and vacancies. Moreover, Fe is distributed over two different crystallographic sites.
Keywords: p-type semiconductors; stannite; solvothermal synthesis; crystal chemistry; spectroscopy; magnetism